LTD expression is independent of glutamate receptor subtype - Granger, Adam J.; Nicoll, Roger A. (Frontiers in Synaptic Neuroscience, 2014)
Long-term depression (LTD) is a form of synaptic plasticity that plays a major role in the activity-dependent reshaping of synaptic transmission. LTD is expressed as a decrease in synaptic AMPA receptor number, though the exact mechanism remains controversial. Several lines of evidence have suggested necessary roles for both the GluA1 and GluA2 subunits, and specifically certain interactions with their cytoplasmic tails. However, it is unclear if either GluA1 or GluA2 are absolutely required for LTD. We tested this hypothesis using constitutive knock-outs and a single-cell molecular replacement of AMPA receptor subunits in mouse hippocampus. We found that neither GluA1 or GluA2 are required for normal of expression of LTD, and indeed a normal decrease in synaptic transmission was observed in cells in which all endogenous AMPA receptors have been replaced by kainate receptors. Thus, LTD does not require removal of specific AMPA receptor subunits, but likely involves a more general modification of the synapse and its ability to anchor a broad range of receptor proteins.